A Comparison Study of Impulsiveness, Cognitive Function, and P300 Components Between Gamma-Hydroxybutyrate and Heroin-Addicted Patients: Preliminary Findings - Zeng, Tingting; Li, Shida; Wu, Li; Feng, Zuxing; Fan, Xinxin; Yuan, Jing; Wang, Xin; Meng, Junyu; Ma, Huan; Zeng, Guanyong; Kang, Chuanyuan; Yang, Jianzhong (Frontiers in Human Neuroscience, 2022)
Purpose: To investigate and compare impulsiveness, negative emotion, cognitive function, and P300 components among gamma-hydroxybutyrate (GHB) addicted patients, heroin dependent patients and methadone maintenance treatment (MMT) subjects. Methods: A total of 48 males including 17 GHB addicts, 16 heroin addicts, 15 MMT subjects and 15 male mentally healthy controls (HC) were recruited. All subjects were evaluated for symptoms of depression, anxiety, impulsiveness and cognitive function through the Patient Health Questionnaire (PHQ-9), the Generalized Anxiety Disorder 7-item (GAD-7), the Barratt Impulsiveness Scale version II (BIS-II), the Beijing version of the Montreal Cognitive Assessment (BJ-MoCA), the behavioral test (response time), and the event-related potential P300 detection. Results: 1. The mean scores of BIS-II in the GHB addiction group, heroin dependence group and MMT group were significantly higher than those of the HC group (F=30.339, P=0.000). 2. The total scores of BJ-MoCA in the GHB addiction group was the highest among the four groups, followed by heroin addiction, the MMT and the HC group (F=27.880, P=0.000). 3. The response time in the GHB addiction group was the longest among the four groups, followed by the heroin addiction, the MMT and the HC group (F=150.499, P=0.000). 4. The amplitude and latency of P300 in GHB addiction subjects were significantly lower and longer than those of the MMT group and the HC group. 5. For the three types of addiction, the P300 amplitudes at Fz, Cz, Pz, T5, and T6 were negatively correlated with the scores of GAD-7, PHQ-9 and BIS-II; the P300 latencies were positively correlated with the response time and negatively coreelated with the scores of the BJ-MoCA. Conclusion: Addictive people were likely to have increased impulsiveness. The cognitive function of the GHB and heroin addicted subjects, including the heroin detoxification and the MMT groups, was severely impaired, especially for the GHB addicted patients. The impairment manifested as abnormalities of the BJ-MoCA, the response time and the P300 components.